Edukasi Penggunaan Media Pembelajaran Pendidikan Jasmani Berbasis Augmented Reality - Ella H Tumaloto; Al Ilham; Oddie Bernanda Rizky; Suriyadi Datau (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2024)
More facilities and infrastructure are needed to improve Physical Education learning in schools. This community service activity aims to overcome this problem at SMAN 1 Dulupi, Boalemo Regency, through education of Penjas learning media based on augmented reality. This activity is designed to provide basic understanding and training in using augmented reality learning media so that the learning process can run effectively despite limited facilities. The methods used in this activity include participatory education and direct assistance. Evaluation is carried out by measuring students' understanding of augmented reality technology and their practical skills. The activity results showed that 96% of participants understood augmented reality technology, and 100% knew how to use augmented reality-based learning media. This activity is expected to encourage the government to develop programs that support integrating technology into learning to facilitate students' understanding.